Droughts and Malnutrition in Africa - Nora Fingado; Steven Poelhekke (Center for Economic Studies and ifo Institute (CESifo), 2023)
How costly are droughts to individuals' nutrition in Africa? We measure severe droughts using a detailed satellite-based vegetation index observed bi-monthly for 0.08° grids between 1982 and 2015. Across 32 African countries, conditional on individual characteristics, timing relative to growing seasons, irrigation, climate, and country-year effects, we show that, unlike recurring droughts, a first-time exposure to a three-month severe drought reduces individuals' body mass index by 2.5%. Droughts are worse for underweight and uneducated individuals. The uneducated are more likely to become unemployed during first-time droughts, whereas both labor reallocation across occupations and migration mitigate the effect of recurring droughts.
Keywords: Q54; I10; I24; O13; J60; 330; drought; nutrition; body-mass index; education; labor reallocation